Perpetrators of Abortion Due to Rape - Fahrur Razi; Riska Nur Hasanah; Rosy Kusuma Dewi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
This study examines the perpetrators of abortion as a result of rape in a review of Islamic law. The formulation of the problem in this study is how the perpetrators of abortion as a result of rape in view of Islamic law. The method used in this research is a qualitative research approach with a descriptive research type. The discussion in this research is in the form of the process of human creation in Islam, the law of women as perpetrators of abortion due to rape in the perspective of the Koran, Hadith, and the perspective of the scholars. This research resulted in the conclusion that abortion should not be done because it is the same as killing a human being. However, on the other hand and in certain circumstances, by adhering to Islamic law through a review of maqashidu al- shari'ah, which has the concept of obtaining benefits and avoiding harm, abortions carried out by women victims of rape can be legally permitted. law, if it does not have the opportunity to endanger the life of the woman.